Lithium secondary battery
The lithium secondary battery design with a separator containing lithium phosphate particles and a high-heat-resistant polymer layer addresses the issue of abnormal heat generation by reducing the reactivity between lithium metal and oxygen gas, enhancing safety and performance.
Patent Information
- Application Number
- JP2021567114
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-12-27
- Filing Date
- 2020-12-01
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2040-12-01
AI Technical Summary
Lithium-ion batteries can experience abnormal heat generation due to internal short circuits, which are exacerbated by the deposition of lithium metal on the negative electrode during charging, leading to further heat and potential safety hazards.
A lithium secondary battery design incorporating a separator with a functional layer containing lithium phosphate particles and a polymer layer to suppress heat generation during abnormal conditions, featuring a specific structure that includes a first layer with lithium phosphate particles and a second layer with a high-heat-resistant polymer, such as aromatic polyamide, to enhance safety.
The proposed separator structure effectively reduces heat generation and suppresses temperature rises during abnormal conditions, improving the safety and performance of lithium-ion batteries by minimizing the reactivity between lithium metal and oxygen gas.
Smart Images

Figure 0007620832000002 
Figure 0007620832000003 
Figure 0007620832000004
Abstract
Description
[Technical field]
[0001] The present disclosure relates to lithium secondary batteries. [Background technology]
[0002] Non-aqueous electrolyte secondary batteries such as lithium-ion batteries may generate abnormal heat due to an internal short circuit. In lithium-ion batteries, when abnormal heat is generated due to an internal short circuit, the battery may generate additional heat due to ionic conduction between the positive and negative electrodes. As one of the measures to suppress such additional heat generation, separators with a shutdown function have been used.
[0003] A separator with a shutdown function melts when abnormal heat generation occurs, blocking the pores in the separator. Blocking the pores in the separator blocks ionic conduction (e.g., lithium ion conduction) between the positive and negative electrodes, suppressing further heat generation.
[0004] A non-aqueous electrolyte secondary battery has been proposed that uses a separator for suppressing heat generation in the battery in the event of an abnormality in the battery (for example, Patent Document 1).
[0005] In non-aqueous electrolyte secondary batteries, a material capable of reversibly absorbing and releasing lithium ions (such as graphite) is generally used as the negative electrode active material. Meanwhile, lithium secondary batteries have also been proposed in which lithium metal is deposited on the negative electrode current collector during charging and the lithium metal dissolves during discharging (for example, Patent Document 2). [Prior art documents] [Patent documents]
[0006] [Patent Document 1] International Publication No. 2019 / 044308 [Patent Document 2] JP 2001-243957 A Summary of the Invention
[0007] As a result of investigations by the present inventors, it was found that a new separator that is highly effective in suppressing heat generation under abnormal conditions is desired for lithium secondary batteries in which lithium metal is deposited on a negative electrode current collector.
[0008] One aspect of the present disclosure relates to a lithium secondary battery including a positive electrode, a negative electrode, a separator disposed between the positive electrode and the negative electrode, and a non-aqueous electrolyte, the negative electrode being an electrode from which lithium metal precipitates during charging and from which the lithium metal dissolves during discharging, the separator including a substrate and a functional layer laminated on the substrate, the functional layer including a first layer including particles of lithium-containing phosphate.
[0009] According to the disclosed embodiment, in a lithium secondary battery in which lithium metal precipitates on the negative electrode during charging, an increase in battery temperature when an abnormality occurs in the battery can be suppressed. [Brief description of the drawings]
[0010] [Figure 1] FIG. 1 is a partially exploded cross-sectional view that illustrates an example of a lithium secondary battery according to the present embodiment. [Diagram 2] FIG. 2 is a cross-sectional view that illustrates a schematic example of a separator of the lithium secondary battery shown in FIG. [Figure 3A] FIG. 3A is a cross-sectional view that illustrates an example of the state of a positive electrode, a negative electrode, and a separator immediately after the assembly of a battery. [Figure 3B] FIG. 3B is a cross-sectional view that illustrates an example of the state of the positive electrode, the negative electrode, and the separator after charging. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] Hereinafter, an embodiment of the present disclosure will be described. In the following description, an embodiment of the present disclosure will be described by way of example, but the present disclosure is not limited to the example described below. In the following description, specific numerical values and materials may be exemplified, but other numerical values and other materials may be applied as long as the effects of the present disclosure can be obtained. In the following description, unless otherwise noted, the term "main component" refers to the component with the highest content (content by mass) in a composition or member (layer, film, or substrate). The content of the main component may be 50% by mass or more.
[0012] As a result of the investigation, the inventors of the present application found that in a lithium secondary battery in which lithium metal is deposited on a negative electrode current collector, a new separator that replaces a conventional separator having a shutdown function is required in order to further suppress heat generation in an abnormal state. As a result of further investigation, the inventors of the present application found that the effect of suppressing heat generation in an abnormal state can be improved by using a separator having a specific structure. The present disclosure is based on these new findings.
[0013] (lithium secondary battery) The lithium secondary battery of this embodiment includes a positive electrode, a negative electrode, a separator disposed between the positive electrode and the negative electrode, and a non-aqueous electrolyte. The negative electrode is an electrode on which lithium metal precipitates during charging and from which the lithium metal dissolves during discharging. The separator includes a substrate and a functional layer laminated on the substrate. The functional layer includes a first layer including particles of phosphate containing lithium. Hereinafter, the particles of phosphate containing lithium may be referred to as "phosphate particles (P)" or "particles (P)". The components of the lithium secondary battery of this embodiment will be described below.
[0014] (Separator) The separator is a sheet-like member having ion permeability and insulation as a whole. The substrate of the separator is also a sheet-like member having ion permeability and insulation. The substrate of the separator may be a laminate of a plurality of sheets including a sheet having ion permeability and insulation.
[0015] The substrate of the separator may be a substrate known as a substrate of a separator for a lithium secondary battery. The substrate of the separator may be a microporous film, a woven fabric, or a nonwoven fabric. Examples of materials for the substrate of the separator include polymers having insulating properties, specifically, polyolefin, polystyrene, polyester, cellulose, and polymers containing them as a basic skeleton. Examples of polyolefins include polyethylene, polypropylene, and copolymers of ethylene and α-olefin. The substrate of the separator may contain polyolefin as a main component, or may be made of only polyolefin.
[0016] The functional layer of the separator may be laminated on the positive electrode side of the two surfaces of the substrate, or on the negative electrode side of the two surfaces of the substrate. The functional layer may be only the first layer, or may include other layers. For example, the functional layer may include the first layer and a second layer described later, or may further include other layers. Typically, the functional layer is formed on only one of the two surfaces of the substrate. That is, typically, the functional layer faces one of the positive and negative electrodes, and the substrate of the separator faces the other electrode. In a typical example, the separator consists of only the substrate and the functional layer.
[0017] The phosphate constituting the phosphate particles (P) may be at least one selected from the group consisting of lithium phosphate (Li3PO4), dilithium hydrogen phosphate (Li2HPO4), and lithium dihydrogen phosphate (LiH2PO4). Among these, lithium phosphate is preferred because of its high effect of suppressing heat generation in the battery under abnormal conditions.
[0018] The first layer may generally contain particles (P) as a main component. The content of particles (P) in the first layer may be in the range of 50% by mass to 99% by mass, 85% by mass to 99% by mass, or 90% by mass to 98% by mass. Within these ranges, the particles P have a sufficient surface area, and it is easy to inactivate lithium at high temperatures. The content may be 50% by mass or more, 70% by mass or more, 85% by mass or more, or 90% by mass or more. The content may be 99% by mass or less, 98% by mass or less, or 95% by mass or less.
[0019] The average particle size of the particles (P) may be in the range of 0.1 μm to 1.0 μm (for example, in the range of 0.1 μm to 0.5 μm, 0.1 μm to 0.2 μm, or 0.1 μm to 0.19 μm). The average particle size of the particles (P) may be 0.1 μm or more or 0.15 μm or more. The average particle size of the particles (P) may be 1.0 μm or less, 0.5 μm or less, 0.3 μm or less, or 0.2 μm or less. By setting the average particle size to 0.1 μm or more, it is possible to ensure sufficient pores for the electrolyte to be immersed. Setting the average particle size to 1.0 μm or less is preferable from the viewpoint of forming a high-density layer of the particles (P). The average particle size of the particles (P) is the median diameter (D 50 ) and is measured by a laser diffraction method (laser diffraction / scattering particle size distribution measuring device). In this specification, the median size or average particle size refers to the volume-based median size unless otherwise specified.
[0020] The first layer may contain solid components other than the particles (P). For example, the first layer may contain a binder, an inorganic substance (e.g., inorganic particles) other than the particles (P), etc. The first layer may further contain a polymer (PL) described later.
[0021] When the first layer contains a binder, the content of the binder in the first layer may be in the range of 1% by mass to 15% by mass, or in the range of 2% by mass to 10% by mass. The content of the binder in the first layer may be 1% by mass or more, or 2% by mass or more. The content of the binder in the first layer may be 15% by mass or less, or 10% by mass or less.
[0022] Examples of the binder contained in the first layer include polyolefins (polyethylene, polypropylene, copolymers of ethylene and α-olefins, etc.), fluorine-containing resins (polyvinylidene fluoride, polytetrafluoroethylene, polyvinyl fluoride, etc.), fluorine-containing rubbers (vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene copolymers, ethylene-tetrafluoroethylene copolymers, etc.), styrene-butadiene copolymers and hydrogenated products thereof, acrylonitrile-butadiene copolymers and hydrogenated products thereof, and acrylonitrile-butadiene-styrene copolymers and hydrogenated products thereof. Further, examples of the binder contained in the first layer include methacrylate-acrylate copolymer, styrene-acrylate copolymer, acrylonitrile-acrylate copolymer, polyvinyl acetate, polyphenylene ether, polysulfone, polyethersulfone, polyphenylene sulfide, polyetherimide, polyamideimide, polyamide, poly N-vinylacetamide, polyester, polyacrylonitrile, cellulose, ethylene-vinyl acetate copolymer, polyvinyl chloride, isoprene rubber, butadiene rubber, polymethyl acrylate, polyethyl acrylate, polyvinyl alcohol, carboxymethyl cellulose, acrylamide, methyl cellulose, guar gum, sodium alginate, carrageenan, xanthan gum, etc. Furthermore, among the above-mentioned binders, those that form salts may be used as salts.
[0023] The functional layer may contain at least one polymer selected from the group consisting of aromatic polyamide, aromatic polyimide, and aromatic polyamideimide. Hereinafter, this at least one polymer may be referred to as "polymer (PL)". Polymer (PL) is preferable in terms of high heat resistance. Polymer (PL) may be composed of only one type of polymer, or may contain multiple types of polymers.
[0024] The functional layer may further include a second layer. The second layer comprises: Aromatic polyamides, It may contain at least one polymer selected from the group consisting of aromatic polyimide and aromatic polyamideimide. That is, the second layer may contain a polymer (PL). The first and second layers may be laminated in the order of the first layer and the second layer from the substrate side. Alternatively, the first and second layers may be laminated in the order of the second layer and the first layer from the substrate side. That is, the second layer may be disposed between the substrate and the first layer. This configuration provides a particularly high effect.
[0025] When the second layer contains a polymer (PL), the content of the polymer (PL) in the second layer may be in the range of 50% by mass to 100% by mass (for example, in the range of 80% by mass to 100% by mass or 90% by mass to 100% by mass). The second layer may be composed of only the polymer (PL). Alternatively, the second layer may contain the polymer (PL) and a polymer other than the polymer (PL), inorganic particles, or other solid components.
[0026] Examples of aromatic polyamides (polymers (PL)) include polymers formed by condensation polymerization of monomers having an aromatic backbone and containing amide bonds in the repeating units. Examples of aromatic polyamides (e.g., wholly aromatic polyamides) include meta-aromatic polyamides (e.g., wholly aromatic polyamides) and para-aromatic polyamides (e.g., wholly aromatic polyamides). Wholly aromatic polyamides are also called aramids.
[0027] Meta-aromatic polyamides are aromatic polyamides with a zigzag molecular skeleton. Meta-aromatic polyamides are, for example, polymers in which meta positions or positions equivalent to meta positions of aromatic skeletons in monomers are bonded by amide bonds. Examples of atomic groups having meta positions or positions equivalent to meta positions include 1,3-phenylene, 3,4'-biphenylene, 1,6-naphthalene, 1,7-naphthalene, 2,7-naphthalene, etc.
[0028] Meta-based aromatic polyamides are obtained, for example, by condensation polymerization of an aromatic diamine having an amino group (-NH2) bonded to the meta position or a position equivalent to the meta position, and an aromatic dicarboxylic acid dichloride having "-COCl" bonded to the meta position or a position equivalent to the meta position. Examples of meta-based aromatic polyamides include polymetaphenylene isophthalamide, poly(metabenzamide), poly(3,4'-benzanilide isophthalamide), poly(metaphenylene-3,4'-biphenylenedicarboxylic acid amide), poly(metaphenylene-2,7-naphthalenedicarboxylic acid amide), and the like.
[0029] Para-type aromatic polyamides are polymers in which the aromatic skeleton of a monomer is bonded at the para position or a position equivalent to the para position by an amide bond. Examples of atomic groups having a bonding position equivalent to the para position include 4,4'-biphenylene, 1,5-naphthalene, and 2,6-naphthalene.
[0030] Para-type aromatic polyamides are obtained, for example, by condensation polymerization of an aromatic diamine having an amino group (-NH2) bonded to the para position or a position equivalent to the para position, and an aromatic dicarboxylic acid dichloride having "-COCl" bonded to the para position or a position equivalent to the para position. Examples of para-type aromatic polyamides include poly(paraphenylene terephthalamide), poly(parabenzamide), poly(4,4'-benzanilide terephthalamide), poly(paraphenylene-4,4'-biphenylenedicarboxylic acid amide), poly(paraphenylene-2,6-naphthalenedicarboxylic acid amide), poly(2-chloro-paraphenylene terephthalamide), etc. Furthermore, examples of aromatic polyamides include copolymers of paraphenylenediamine and 2,6-dichloroparaphenylenediamine with terephthalic acid dichloride, etc.
[0031] Examples of aromatic polyimides (polymers (PL)) include polymers formed by condensation polymerization of monomers having an aromatic backbone and containing imide bonds in the repeating units. Aromatic polyimides are obtained, for example, by condensation polymerization of an aromatic compound that is a tetracarboxylic dianhydride and an aromatic diamine. Examples of aromatic compounds that are tetracarboxylic dianhydrides include pyromellitic dianhydride, 3,3',4,4'-diphenylsulfonetetracarboxylic dianhydride, 3,3',4,4'-benzophenonetetracarboxylic dianhydride, 2,2'-bis(3,4 dicarboxyphenyl)hexafluoropropane, 3,3',4,4'-biphenyltetracarboxylic dianhydride, and the like. Examples of aromatic diamines include 4,4'-diaminodiphenyl ether, paraphenylenediamine, 3,3'-methylenedianiline, 3,3'-diaminobenzophenone, 3,3'-diaminobenzosulfone, and the like.
[0032] Examples of aromatic polyamideimides (polymers (PL)) include polymers formed by condensation polymerization of monomers having an aromatic backbone and containing amide bonds and imide bonds. Aromatic polyamideimides can be obtained, for example, by condensation polymerization of an aromatic compound (A) that is a tricarboxylic acid anhydride with an aromatic diisocyanate. Furthermore, aromatic polyamideimides can also be obtained by condensation polymerization of an aromatic compound (B) in which a carboxylic acid anhydride group (two carboxyl groups that have been dehydrated and condensed) and "-COCl" are bonded to an aromatic ring with an aromatic diamine.
[0033] Examples of the aromatic compound (A) include trimellitic anhydride, etc. Examples of the aromatic diisocyanate include 4,4'-diphenylmethane diisocyanate, 2,4-tolylene diisocyanate, 2,6-tolylene diisocyanate, m-xylene diisocyanate, etc. Examples of the aromatic compound (B) include trimellitic anhydride chloride, etc. Examples of the aromatic diamine include the aromatic diamines mentioned above.
[0034] Aromatic polyamides, aromatic polyimides, and aromatic polyamideimides are known as polymers (polymers or resins in another respect) with high heat resistance. From the viewpoint of heat resistance, aramids, i.e., meta-aramids (meta-fully aromatic polyamides) and para-aramids (para-fully aromatic polyamides), are preferred. A preferred example of the polymer (PL) is meta-aramid. Known aromatic polyamides, aromatic polyimides, and aromatic polyamideimides may be used as the polymer (PL).
[0035] Generally, a polymer having higher heat resistance than the main component of the separator substrate (e.g., the above-mentioned polymer) is selected as the polymer (PL). Aromatic polyamide, aromatic polyimide, and aromatic polyamideimide usually have higher heat resistance than the above-mentioned polymers as examples of the separator substrate material.
[0036] The functional layer may further contain inorganic particles other than the particles (P). Hereinafter, the inorganic particles may be referred to as "inorganic particles (F)". The inorganic particles (F) are preferably made of an inorganic material having a higher melting point than the particles (P). The inorganic particles (F) may be contained in the first layer and / or the second layer.
[0037] A preferred example of the inorganic particles (F) is a particle composed of an insulating inorganic compound that does not melt or decompose when the battery generates abnormal heat. The inorganic particles (F) may be inorganic particles that are generally used as inorganic fillers. Examples of materials for the inorganic particles (F) include oxides, oxide hydrates, hydroxides, nitrides, carbides, sulfides, etc., which may contain metal elements. The volume-based median diameter (D 50 ) may be 0.2 μm or more and 2 μm or less.
[0038] Examples of oxides and oxide hydrates include aluminum oxide (alumina), boehmite (Al2O3H2O or AlOOH), magnesium oxide, titanium oxide, zirconium oxide, silicon oxide, yttrium oxide, zinc oxide, etc. Examples of nitrides include silicon nitride, aluminum nitride, boron nitride, titanium nitride, etc. Examples of carbides include silicon carbide, boron carbide, etc. Examples of sulfides include barium sulfate, etc. Examples of hydroxides include aluminum hydroxide, etc. It is desirable that the melting point of a substance that melts after being modified to alumina, such as boehmite, after modification is higher than the melting point of the particles (P).
[0039] The material of the inorganic particles (F) may be a porous aluminosilicate such as zeolite, a layered silicate such as talc, barium titanate (BaTiO3), strontium titanate (SrTiO3), etc. From the viewpoint of insulation and heat resistance, etc., the material of the inorganic particles (F) may be at least one selected from the group consisting of aluminum oxide, boehmite, talc, titanium oxide, and magnesium oxide.
[0040] The second layer may contain inorganic particles (F) as a main component. The content of the inorganic particles (F) in the second layer may be in the range of 50% by mass to 99% by mass (for example, in the range of 85% by mass to 99% by mass). In this case, the second layer may contain a binder. Examples of the binder include the binders exemplified in the description of the first layer. The content of the inorganic particles (F) in the second layer may be 50% by mass or more, 70% by mass or more, 85% by mass or more, or 90% by mass or more. The content may be 99% by mass or less, 98% by mass or less, or 95% by mass or less.
[0041] The thickness of the functional layer may be in the range of 0.2 μm to 10 μm (for example, in the range of 1 μm to 8 μm, in the range of 2 μm to 4 μm, or in the range of 4 μm to 10 μm). The thickness of the functional layer may be 0.2 μm or more, 0.3 μm or more, 0.5 μm or more, 1 μm or more, 2 μm or more, 3 μm or more, or 4 μm or more. The thickness of the functional layer may be 10 μm or less, 8 μm or less, 7 μm or less, or 5 μm or less. When the thickness of the functional layer is 0.2 μm or more, it is advantageous in terms of suppressing an increase in the battery temperature in the event of an abnormality. When the thickness of the functional layer is 10 μm or less, it is advantageous in terms of the electrical characteristics of the battery.
[0042] When the functional layer includes a first layer and a second layer, the thickness of the first layer may be 0.2 μm or more, may be 0.3 μm or more, may be 0.5 μm or more, preferably 1 μm or more, more preferably 2 μm or more, more preferably 3 μm or more, and more preferably 4 μm or more. The thickness of the first layer may be 10 μm or less, 8 μm or less, 7 μm or less, or 5 μm or less. The thickness of the second layer may be 0.2 μm or more, may be 0.3 μm or more, may be 0.5 μm or more, preferably 1 μm or more, more preferably 2 μm or more, more preferably 3 μm or more, and more preferably 4 μm or more. The thickness of the second layer may be 10 μm or less, 8 μm or less, 7 μm or less, or 5 μm or less.
[0043] The porosity of the separator may be in the range of 30% to 70%. Similarly, the porosity of each of the layers constituting the separator (substrate, functional layer, first layer, second layer) may be in the range of 30% to 70%. The porosity is calculated by the following formula. Porosity (%)=100-(100×ρ1 / ρ0) [ρ0 indicates the density of a layer without voids. ρ0 may be obtained from the physical properties of the constituent materials, or may be obtained by forming a layer so that voids are not formed and measuring the thickness, area, and weight of the layer. ρ1 indicates the density of an actual measured member. ρ1 may be obtained by measuring the thickness, area, and weight of the member.] A preferable example of the separator satisfies all of the following conditions (1) to (4). (1) The functional layer is formed on only one side of the substrate. The functional layer has a first layer and a second layer. (2) The particles (P) are lithium phosphate. The content of the lithium phosphate particles in the first layer is in the range of 85% by mass to 99% by mass. (3) The content of the polymer (PL) in the second layer is 80% by mass to 100% by mass (for example, in the range of 90% by mass to 100% by mass). The polymer (PL) is preferably a wholly aromatic polyamide (aramid), for example, a meta-based wholly aromatic polyamide (meta-based aramid). (4) The thicknesses of the first and second layers are each within the ranges described above. The above preferred example of the separator may further satisfy the following conditions. (5) The average particle size of the particles (P) is in the range of 0.1 μm to 1.0 μm (for example, in the above range).
[0044] The lithium secondary battery of this embodiment uses, as the negative electrode, a negative electrode in which lithium metal is deposited directly or through another layer on the negative electrode current collector during charging. When such a lithium metal deposition type negative electrode is used, the temperature rise is more likely to accelerate when the battery temperature rises abnormally than when a non-lithium metal deposition type negative electrode is used. The cause is not clear at present, but is speculated as follows. That is, when the battery temperature rises abnormally, oxygen gas is released by decomposition of the positive electrode active material. The released oxygen gas reaches the negative electrode and reacts with the lithium metal of the negative electrode. Since the reactivity of lithium metal and oxygen gas is very high, it is thought that the temperature rise is greatly accelerated by their reaction.
[0045] The separator includes a first layer containing phosphate particles (P). This first layer can suppress further temperature rise when the battery temperature rises abnormally. The mechanism is not clear at present. One possibility is that when the battery temperature rises abnormally, the particles (P) react with the lithium metal of the negative electrode, reducing the reactivity of the lithium metal surface.
[0046] When the functional layer includes the second layer, the second layer can function as a layer having heat resistance. Therefore, it is considered that the second layer suppresses the thermal contraction of the separator when the battery temperature rises abnormally. Although the reason why the first layer and the second layer show a remarkable effect when used together is not clear at present, as shown in the examples, a remarkable effect can be obtained by combining the first layer and the second layer.
[0047] The separator can be produced by forming a functional layer on a substrate. The first layer can be formed, for example, by the following method. First, a solid component containing particles (P) is mixed with a liquid component (dispersion medium) to form a slurry. Next, the slurry is applied to the substrate or the second layer to form a coating film, and the coating film is then dried. In this manner, the first layer can be formed. There is no particular limitation on the liquid used to form the slurry. Examples of such liquids include N-methyl-2-pyrrolidone, etc.
[0048] The second layer can be formed, for example, by the following method. First, a coating liquid is formed by mixing a solid component including a polymer (PL) and particles (PM) with a liquid component (dispersion medium / solvent). Examples of the liquid component include N-methyl-2-pyrrolidone, etc. Here, the particles (PM) are particles for making the second layer a porous layer by removing them later. For the particles (PM), particles that dissolve in a solvent in which the polymer (PL) does not dissolve can be used. Examples of the particles (PM) include lithium chloride and calcium chloride. Next, the coating liquid is applied to a substrate to form a coating film, and the coating film is then dried. Thereafter, the coating film is washed with a washing liquid (e.g., water) to dissolve and remove the particles (PM). In this manner, the second layer can be formed.
[0049] Each step in forming the first and second layers is not particularly limited, and known methods can be applied. For example, the application of the slurry and coating liquid may be performed by known methods such as a method using a bar coater. In addition, drying may be performed by known methods such as drying by heating or natural drying.
[0050] (Negative electrode) The negative electrode is an electrode in which lithium metal is deposited during charging of the battery and in which lithium metal dissolves during discharging of the battery. During charging, lithium metal is deposited directly on the negative electrode current collector, or on the negative electrode current collector via a coating layer. Hereinafter, the negative electrode member on whose surface lithium metal is deposited may be referred to as "negative electrode substrate". The negative electrode substrate includes at least a negative electrode current collector. The negative electrode substrate may be composed of only a negative electrode current collector, or may include a negative electrode current collector and a coating layer disposed on the negative electrode current collector. This negative electrode substrate may be used in the manufacture of the lithium secondary battery of this embodiment. The coating layer disposed on the negative electrode current collector will be described later.
[0051] The lithium metal deposited during charging may contain trace components other than lithium. The lithium metal is deposited mainly on the surface of the negative electrode facing the positive electrode. The deposited lithium metal originates from the lithium ions released from the positive electrode into the non-aqueous electrolyte during charging. The lithium metal deposited on the negative electrode dissolves again in the non-aqueous electrolyte during discharging. The lithium ions dissolved in the non-aqueous electrolyte are taken up by the positive electrode during discharging.
[0052] The negative electrode current collector is made of a conductive material (e.g., a metal material) other than lithium metal and lithium alloys. The negative electrode current collector may be made of a metal material that does not react with lithium metal (i.e., a metal material that does not form an alloy or intermetallic compound with lithium metal). Examples of such metal materials include copper (Cu), nickel (Ni), iron (Fe), stainless steel (SUS), and the like. The material that makes up the negative electrode current collector may be copper.
[0053] The form of the negative electrode current collector is not particularly limited, and may be a porous or non-porous sheet (i.e., foil, film, etc.). The surface of the negative electrode current collector may be uneven. When a copper-containing foil is used as the negative electrode current collector, the foil may contain copper as a main component, or may be substantially composed of copper only. The thickness of the negative electrode current collector is not particularly limited, and may be, for example, in the range of 5 to 20 μm.
[0054] As described above, the negative electrode base material may include a negative electrode current collector and a coating layer disposed on the negative electrode current collector. The coating layer may be a lithium metal layer. That is, in this case, the lithium metal layer is disposed on the negative electrode current collector in advance. Then, lithium metal is further precipitated on the coating layer (lithium metal layer) by charging, and the lithium metal layer becomes thicker. There is no particular limitation on the method of disposing the lithium metal layer (coating layer) on the negative electrode current collector in advance. For example, lithium metal may be rolled into a foil shape by roll pressing, and the foil-shaped lithium metal may be transferred onto the negative electrode current collector. Alternatively, lithium metal may be vapor-deposited on the negative electrode current collector.
[0055] The coating layer disposed on the negative electrode current collector may be a layer capable of absorbing lithium ions. This layer may be hereinafter referred to as a "lithium ion absorbing layer." The lithium ion absorbing layer absorbs lithium ions during charging. When this layer is filled with lithium ions, the lithium ions are precipitated on the layer as lithium metal.
[0056] The lithium ion storage layer includes a material capable of absorbing lithium ions. For example, a material used as a negative electrode active material of a lithium ion battery may be used as such a material. Specifically, a carbon material capable of reversibly absorbing and releasing lithium ions, a metal alloyed with lithium, an inorganic compound absorbing lithium ions, etc. may be used. Carbon materials have the advantage of being low cost. Examples of carbon materials include natural graphite, artificial graphite, non-graphitizable carbon, easily graphitizable carbon, carbon black, carbon nanotubes, etc.
[0057] The coating layer may be a layer of a metal (including a metalloid such as silicon) that alloys with lithium. Examples of metals that form such metal layers include aluminum, zinc, silicon, tin, and the like.
[0058] Examples of inorganic compounds that absorb lithium ions include oxides such as silicon compounds and tin compounds, and spinel compounds such as lithium titanate.
[0059] When forming a lithium ion occlusion layer using particles of a material capable of occluding lithium ions, a slurry containing the particles and a liquid component is prepared, and the lithium ion occlusion layer is formed using the slurry. The slurry may contain other substances (binders) as necessary. The binder may be a binder used in a positive electrode, which will be described later, or a known binder. The lithium ion occlusion layer may be formed by the same method as the method for forming a general negative electrode active material layer.
[0060] When the lithium ion occlusion layer is formed using a particulate carbon material or metal compound, the thickness of the lithium ion occlusion layer may be 5 μm or more and 20 μm or less (e.g., 10 μm or less).When a metal layer is used as the lithium ion occlusion layer, the thickness of the lithium ion occlusion layer may be 0.01 μm or more and 1 μm or less (e.g., 0.1 μm or less).
[0061] The movement of electrons in the negative electrode during charging and discharging is mainly due to the deposition and dissolution of lithium metal in the negative electrode. Specifically, 70 to 100% (e.g., 80 to 100% or 90 to 100%) of the movement of electrons (current in another respect) in the negative electrode during charging and discharging is due to the deposition and dissolution of lithium metal. That is, the negative electrode of this embodiment is different from a negative electrode in which the movement of electrons in the negative electrode during charging and discharging is mainly due to the absorption and release of lithium ions by the negative electrode active material (such as graphite). That is, the amount of lithium metal present in the coating layer and the amount of lithium ions that can be absorbed in the coating layer are sufficiently smaller than the amount of lithium metal precipitated in the negative electrode by charging.
[0062] When the negative electrode includes a lithium ion storage layer, the open circuit potential of the negative electrode at full charge may be 70 mV or less with respect to lithium metal (dissolution and deposition potential of lithium). Lithium metal is deposited in a negative electrode with an open circuit potential of 70 mV or less with respect to lithium metal. Therefore, when the open circuit potential of the negative electrode at full charge is 70 mV or less with respect to lithium metal, it can be said that lithium metal is present on the surface of the lithium ion storage layer at full charge. That is, the negative electrode exhibits capacity due to deposition and dissolution of lithium metal. Here, when the rated capacity of the battery is C, the battery is charged to a charge state of, for example, 0.98×C or more. The open circuit potential of the negative electrode at full charge may be measured by disassembling a fully charged battery under an argon atmosphere, removing the negative electrode, and assembling a cell with lithium metal as a counter electrode. The non-aqueous electrolyte of the cell may have the same composition as the non-aqueous electrolyte in the disassembled battery.
[0063] (Non-aqueous electrolyte) The non-aqueous electrolyte contains, for example, a non-aqueous solvent, and lithium ions and anions dissolved in the non-aqueous solvent. The non-aqueous electrolyte may be in a liquid state or a gel state.
[0064] The liquid non-aqueous electrolyte is prepared by dissolving a lithium salt in a non-aqueous solvent, which generates lithium ions and anions.
[0065] The gelled non-aqueous electrolyte contains a lithium salt and a matrix polymer, or a lithium salt, a non-aqueous solvent, and a matrix polymer. For the matrix polymer, for example, a polymer material that absorbs the non-aqueous solvent and gels is used. Examples of the polymer material include fluororesin, acrylic resin, and polyether resin.
[0066] The lithium salt or anion may be any known anion used in non-aqueous electrolytes for lithium secondary batteries. - , ClO4 - , PF6 - , CF3SO3 - , CF3CO2 - , anions of imides, anions of oxalate complexes, etc. Examples of anions of imides include N(SO2CF3)2 - , N(C m F 2m+1 SO2) x (C n F 2n+1 SO2)y - (m and n are each independently an integer of 0 or 1 or more, and x and y are each independently 0, 1, or 2, and x+y=2 is satisfied.) The anion of the oxalate complex may contain boron and / or phosphorus. Examples of the anion of the oxalate complex include bisoxalate borate anion, BF2(C2O4) - , PF4(C2O4) - , PF2(C2O4)2 - The non-aqueous electrolyte may contain one of these anions alone or two or more of them.
[0067] The non-aqueous electrolyte may include lithium ions and anions, and the anions may include at least an anion of an oxalate complex. The anion of the oxalate complex may be a bisoxalate borate anion.
[0068] From the viewpoint of suppressing lithium metal precipitation in a dendritic form, the non-aqueous electrolyte preferably contains at least an anion of an oxalate complex. The interaction between the anion of the oxalate complex and lithium makes it easier for the lithium metal to be uniformly precipitated in the form of fine particles. This makes it easier to suppress localized precipitation of the lithium metal. The anion of the oxalate complex may be combined with another anion. The other anion may be PF6 - and / or the anion of an imide.
[0069] Examples of the non-aqueous solvent include esters, ethers, nitriles, amides, and halogen-substituted products thereof. The non-aqueous electrolyte may contain one or more of these non-aqueous solvents. Examples of the halogen-substituted products include fluorides.
[0070] Examples of esters include carbonate esters and carboxylate esters. Examples of cyclic carbonate esters include ethylene carbonate, propylene carbonate, and fluoroethylene carbonate (FEC). Examples of chain carbonate esters include dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), and diethyl carbonate. Examples of cyclic carboxylate esters include γ-butyrolactone and γ-valerolactone. Examples of chain carboxylate esters include methyl acetate, ethyl acetate, methyl propionate, and methyl fluoropropionate.
[0071] Examples of the ether include cyclic ethers and chain ethers. Examples of the cyclic ethers include 1,3-dioxolane, 4-methyl-1,3-dioxolane, tetrahydrofuran, and 2-methyltetrahydrofuran. Examples of the chain ethers include 1,2-dimethoxyethane, diethyl ether, ethyl vinyl ether, methyl phenyl ether, benzyl ethyl ether, diphenyl ether, dibenzyl ether, 1,2-diethoxyethane, and diethylene glycol dimethyl ether.
[0072] The concentration of the lithium salt in the non-aqueous electrolyte is, for example, 0.5 mol / L or more and 3.5 mol / L or less. The concentration of the anion in the non-aqueous electrolyte may be 0.5 mol / L or more and 3.5 mol / L or less. The concentration of the anion of the oxalate complex in the non-aqueous electrolyte may be 0.05 mol / L or more and 1 mol / L or less.
[0073] The non-aqueous electrolyte may contain an additive. The additive may form a coating on the negative electrode. The coating derived from the additive is formed on the negative electrode, which makes it easier to suppress the generation of dendrites. Examples of such additives include vinylene carbonate, FEC, vinyl ethyl carbonate (VEC), and the like.
[0074] (positive electrode) The positive electrode includes, for example, a positive electrode current collector and a positive electrode active material layer disposed on the positive electrode current collector. The positive electrode active material layer includes a positive electrode active material, and further includes other materials (e.g., a conductive material, a binder, etc.) as necessary. The other materials may be known materials. The positive electrode active material layer may be disposed on only one side of the positive electrode current collector, or may be disposed on both sides. The positive electrode can be formed, for example, by the following method. First, a positive electrode mixture slurry containing a positive electrode active material and other materials (e.g., a conductive material and a binder) is prepared. Next, the slurry is applied to the surface (one side or both sides) of the positive electrode current collector to form a laminate including the positive electrode current collector and a coating film. Next, the coating film of the laminate is dried, and then the laminate is rolled. In this manner, a positive electrode is obtained.
[0075] Examples of the positive electrode active material include layered rock salt type composite oxides. Examples of the layered rock salt type composite oxides include Li a CoO2, Li a NiO2, Li a MnO2, Li a Co b M 1-b O c (M is at least one selected from the group consisting of Na, Mg, Sc, Y, Mn, Fe, Ni, Cu, Zn, Al, Cr, Pb, Sb, and B), LiMPO 4、 (M is at least one selected from the group consisting of Na, Mg, Sc, Y, Mn, Fe, Co, Ni, Cu, Zn, Al, Cr, Pb, Sb, and B), etc. are included. Here, 0 < a ≤ 1.1, 0 ≤ b ≤ 0.9, and 2 ≤ c ≤ 2.3. Note that the value of a indicating the composition ratio of lithium increases or decreases by charge and discharge.
[0076] The layered rock salt type composite oxide containing nickel element is advantageous in terms of high capacity and low cost. Such a composite oxide is represented by, for example, the general formula: Li a Ni x Co y M 1-x-y O2. Cobalt is advantageous for the long life of the battery, etc.
[0077] The above general formula satisfies, for example, 0.97 < a ≤ 1.2, 0.5 ≤ x ≤ 1.0, and 0 ≤ y ≤ 0.1. In order to increase the capacity, 0.8 ≤ x ≤ 1.0 may be satisfied. Here, M is, for example, at least one selected from the group consisting of Mn, Al, W, Mg, Mo, Nb, Ti, Si, and Zr. Using aluminum for M is advantageous for improving thermal stability, etc. The atomic ratio Co / Al may be set to 0 to 1.0. Note that manganese, tungsten, niobium, magnesium, zirconium, etc. are considered to contribute to the stabilization of the crystal structure.
[0078] Examples of the conductive material include carbon materials such as carbon black (CB), acetylene black (AB), ketjen black (KB), carbon nanotubes (CNT), graphite, etc. These may be used alone or in combination of two or more.
[0079] Examples of the binder include fluororesins (polytetrafluoroethylene, polyvinylidene fluoride, etc.), polyacrylonitrile (PAN), polyimide resins, acrylic resins, polyolefin resins, etc. These may be used alone or in combination of two or more.
[0080] Examples of materials for the positive electrode current collector include metal materials such as Al, Ti, and alloys thereof (such as Al alloys), and stainless steel (SUS). Examples of the form of the positive electrode current collector include a porous or non-porous sheet. The positive electrode current collector may be a sheet made of a metal material, such as a metal foil (i.e., a metal film) or a metal mesh. The surface of the positive electrode current collector may be coated with a carbon material such as carbon.
[0081] The lithium secondary battery of this embodiment may be cylindrical, rectangular, or of other shapes. The lithium secondary battery of this embodiment includes a battery case according to the shape. A known battery case can be used as the battery case. The lithium secondary battery of this embodiment may include other components (for example, known components) as necessary.
[0082] An electrode group and a non-aqueous electrolyte are disposed in the battery case. The electrode group includes a positive electrode, a negative electrode, and a separator disposed between the positive electrode and the negative electrode. The electrode group is formed according to the shape of the battery. For example, in the case of a cylindrical battery, the electrode group is usually formed by winding the positive electrode, the negative electrode, and the separator so that the separator is disposed between the positive electrode and the negative electrode.
[0083] The method for manufacturing the lithium secondary battery of this embodiment is not particularly limited, and known techniques can be used as necessary. In one example of the manufacturing method, first, an electrode group is formed. Next, the electrode group and the non-aqueous electrolyte are placed in the case body of the battery case. If necessary, at an appropriate stage, either the positive electrode or the negative electrode is electrically connected to the case body, and the other is electrically connected to the sealing body. Next, the case body is sealed using a gasket and a sealing body. In this manner, a lithium secondary battery can be manufactured.
[0084] Hereinafter, an example of the lithium secondary battery of the present embodiment will be specifically described with reference to the drawings. The above-mentioned components can be applied to the components of the lithium secondary battery of the example described below. In addition, the components of the example described below can be modified based on the above description. In addition, the matters described below may be applied to the above-mentioned embodiment.
[0085] (Embodiment 1) A partially exploded cross-sectional view of an example of the configuration of a lithium secondary battery according to the present disclosure is shown typically in Fig. 1. The lithium secondary battery 100 shown in Fig. 1 is a cylindrical secondary battery.
[0086] The lithium secondary battery 100 is a wound battery, and includes a wound electrode group 40 and a non-aqueous electrolyte. The electrode group 40 includes a strip-shaped positive electrode 10, a strip-shaped negative electrode 20, and a separator 30. The separator 30 is disposed between the positive electrode 10 and the negative electrode 20. A positive electrode lead 13 is connected to the positive electrode 10. A negative electrode lead 23 is connected to the negative electrode 20.
[0087] One end of the positive electrode lead 13 is connected to the positive electrode 10, and the other end is connected to a sealing body 50. The sealing body 50 includes a positive electrode terminal 50a. Typically, the sealing body 50 includes a mechanism that operates as a safety valve when the internal pressure of the battery increases.
[0088] One end of the negative electrode lead 23 is connected to the negative electrode 20, and the other end is connected to the bottom of the case (case body) 60. The case 60 functions as a negative electrode terminal. The case 60 is a cylindrical can with a bottom. The case 60 is made of metal, for example, iron. The inner surface of the iron case 60 is usually nickel-plated. An upper insulating ring 81 and a lower insulating ring 82 made of resin are disposed on the upper and lower parts of the electrode group 40, respectively. The electrode group 40 and a non-aqueous electrolyte are disposed inside the case 60. The case 60 is sealed by a sealing body 50 and a gasket 70.
[0089] An example of the separator 30 is shown in FIG. 2. The separator 30 includes a substrate 31 and a functional layer 32 laminated on the substrate 31. The functional layer 32 includes a first layer 32a and a second layer 32b disposed between the substrate 31 and the first layer 32a. The first layer 32a and the second layer 32b are each the layers described above. The functional layer 32 may be disposed on one of the two surfaces of the substrate 31 that faces the positive electrode 10, or on the other that faces the negative electrode 20.
[0090] FIG. 3A shows a schematic diagram of the state of the positive electrode 10, the negative electrode 20, and the separator 30 in an example of an electrode group 40 immediately after the battery is assembled. The positive electrode 10 includes a positive electrode current collector 11 and a positive electrode active material layer 12 formed on the positive electrode current collector 11. The negative electrode 20 in the example immediately after the battery is assembled is composed of only a negative electrode substrate 21. The negative electrode substrate 21 includes at least a negative electrode current collector, and may be composed of only a negative electrode current collector. In the example shown in FIG. 3A, a space S exists between the negative electrode substrate 21 and the separator 30, but the space S may exist in another location or may not exist.
[0091] FIG. 3B shows a schematic diagram of the state of the positive electrode 10, the negative electrode 20, and the separator 30 in an example of an electrode group 40 after sufficient charging. As shown in FIG. 3B, lithium metal 22 is deposited on the surface of the negative electrode substrate 21. The volume of the negative electrode 20 increases due to the deposition of lithium metal 22. At least a portion of the deposited lithium metal 22 is released as lithium ions during discharge. In this manner, charging and discharging are repeated.
[0092] FIG. 1 shows a cylindrical lithium secondary battery having a wound electrode group. However, the lithium secondary battery of this embodiment may be a lithium secondary battery of another form. For example, the lithium secondary battery of this embodiment may be of various shapes such as a cylindrical shape, a coin shape (including a button shape), a rectangular shape, a sheet shape, or a flat shape depending on the application. The shape of the electrode group is not particularly limited, and may be a wound type or a layered type. In addition, a known configuration may be applied to configurations other than those specific to this embodiment.
[0093] <Example> The lithium secondary battery of this embodiment will be described in more detail with reference to Examples In these Examples, seven types of lithium secondary batteries (batteries A1 to A5, battery C1, and battery R1) were produced and evaluated.
[0094] (Battery A1) A polyethylene porous film (thickness: 12 μm) was used as the substrate of the separator of the battery A1. A second layer and a first layer were formed in this order on the substrate to obtain a separator in which a functional layer was laminated on the substrate.
[0095] The second layer was formed as follows. First, N-methyl-2-pyrrolidone (NMP) and calcium chloride were mixed in a mass ratio of 94.2:5.8. The mixture was heated to about 80°C to completely dissolve calcium chloride. Then, the solution was returned to room temperature, and 2200 g was collected, and 0.6 mol of paraphenylenediamine (PPD) was added to completely dissolve it. While the solution was kept at about 20°C, 0.6 mol of terephthalic acid dichloride (TPC) was added little by little. The obtained solution was aged at about 20°C for 1 hour to obtain a polymerization liquid. Next, 100 g of this polymerization liquid was mixed with an N-methyl-2-pyrrolidone solution in which 5.8 mass% of calcium chloride was dissolved, and a solution (coating liquid) in which the concentration of paraphenylene terephthalamide (PPTA), which is an aromatic polyamide (aramid), was 2 mass% was obtained.
[0096] Next, the coating solution was applied to the substrate by a slot die method so that the thickness after drying was 2 μm to form a coating film. Next, the substrate on which the coating film was formed was left for 1 hour in an atmosphere at a temperature of 25° C. and a relative humidity of 70% to precipitate the aromatic polyamide. Next, NMP and calcium chloride in the coating film were removed by washing with water. Next, the coating film was dried at 60° C. for 5 minutes to form a second layer (thickness 2 μm).
[0097] The first layer was formed as follows. First, lithium phosphate (Li3PO4) particles and poly(N-vinylacetamide) (PNVA) were mixed in a mass ratio of 100:8 to obtain a mixture. The lithium phosphate particles used had a volume-based median diameter of 0.19 μm. Water (ion-exchanged water) was added to the obtained mixture and stirred to prepare a slurry (coating liquid) with a solid content concentration of 12 mass%. Next, the slurry was coated on the second layer by microgravure coating to form a coating film. Next, the coating film was dried in a drying oven attached to the coater. In this way, the first layer (thickness 2 μm) was formed. In this way, the separator of the battery A1 was formed.
[0098] The positive electrode was prepared as follows. First, the positive electrode active material, acetylene black, and polyvinylidene fluoride were mixed in a mass ratio of 100:0.75:0.6, and N-methyl-2-pyrrolidone was added and stirred to prepare a slurry. The positive electrode active material was LiNi 0.9 Co 0.05 Al 0.05 O2 was used. Next, the slurry was applied to both sides of a positive electrode current collector to form a coating film, and a laminate including the positive electrode current collector and the coating film was obtained. For the positive electrode current collector, aluminum foil was used. Next, the coating film of the laminate was dried, and then the laminate was rolled with a rolling roller to obtain a positive electrode.
[0099] The negative electrode was prepared by cutting an electrolytic copper foil (thickness: 10 μm) to a predetermined electrode size.
[0100] The non-aqueous electrolyte was prepared in the following manner. First, a solvent was prepared by mixing fluoroethylene carbonate (FEC), ethyl methyl carbonate (EMC), and DMC (dimethyl carbonate) in a volume ratio of 20:5:75. LiPF6 and LiBF2(C2O4) were dissolved in this solvent to a concentration of 1 mol / L and 0.5 mol / L, respectively, to prepare a non-aqueous electrolyte (non-aqueous electrolyte solution).
[0101] The battery A1 was produced as follows. First, an aluminum tab was attached to the positive electrode, and a nickel tab was attached to the negative electrode. Next, the positive electrode, the negative electrode, and the separator were arranged so that the separator was arranged between the positive electrode and the negative electrode, and they were wound together in a spiral shape. At this time, the separator was arranged so that the functional layer of the separator faced the positive electrode. In addition, in the battery produced below, the separator was similarly arranged so that the functional layer faced the positive electrode. In this way, a wound electrode group was obtained. The electrode group was housed in a bag-shaped exterior body formed of a laminate sheet including an aluminum layer. After a non-aqueous electrolyte was injected into the exterior body, the exterior body was sealed to obtain the battery A1.
[0102] (Battery A2) Battery A2 was fabricated using the same materials and methods as Battery A1, except that the first layer contained lithium phosphate particles with a volumetric median diameter of 0.28 μm.
[0103] (Battery A3) Battery A3 was produced using the same materials and methods as Battery A1, except for the thickness of the first layer, which was 4 μm.
[0104] (Battery A4) Battery A4 was produced using materials and by the same method as those of Battery A1, except that the first layer was made of a different material.
[0105] The first layer of the battery A4 was formed as follows. First, lithium phosphate (Li3PO4) particles and aluminum oxide (Al2O3) particles were mixed in a mass ratio of 1:1 to obtain a mixture. The lithium phosphate particles had a volumetric median diameter of 2.8 μm. The aluminum oxide particles had a volumetric median diameter of 4.2 μm. The median diameter of both particles as a whole was 0.35 μm. N-methyl-2-pyrrolidone was added to the obtained mixture and stirred to prepare a slurry (coating liquid) with a solid content concentration of 12 mass%. Next, the slurry was used to form the first layer (2 μm thick) of the battery A4 in the same manner as the first layer of the battery A1.
[0106] (Battery A5) Battery A5 was produced using materials and by a method similar to those of Battery A1, except that the first layer was made of a different material.
[0107] The first layer of the battery A5 was formed as follows. First, aluminum oxide (Al2O3) particles and poly-N-vinylacetamide (PNVA) were mixed in a mass ratio of 100:8 to obtain a mixture. The aluminum oxide particles used had a volume-based median diameter of 0.42 μm. N-methyl-2-pyrrolidone was added to the obtained mixture and stirred to prepare a slurry (coating liquid) with a solid content concentration of 12 mass %. Next, the first layer (thickness 2 μm) of the battery A5 was formed using the slurry in the same manner as the first layer of the battery A1.
[0108] (Battery C1) Battery C1 was produced using the same materials and methods as battery A1, except that the first layer was not formed. The functional layer of battery C1 was composed of only the second layer. Battery C1 is a comparative example.
[0109] (Battery R1) Battery R1 was prepared using the same materials and methods as battery A1, except that the negative electrode and separator were different. Battery R1 is a reference battery. The separator of battery R1 was prepared using the same materials and methods as battery A1, except that the first layer was not formed. That is, the functional layer of battery R1 consists only of the second layer.
[0110] The negative electrode of the battery R1 was a type that does not precipitate lithium metal. Specifically, the negative electrode was prepared as follows. First, artificial graphite (negative electrode active material), sodium carboxymethylcellulose, and styrene-butadiene rubber powder were mixed in water at a solid content mass ratio of 98:1:1 to prepare a slurry. Next, the slurry was applied to both sides of a negative electrode collector made of copper foil to form a coating film, thereby obtaining a laminate including the negative electrode collector and the coating film. Copper foil (thickness 8 μm) was used for the negative electrode collector. Next, the coating film of the laminate was dried, and then the laminate was rolled with a rolling roller to obtain a negative electrode.
[0111] (Nail penetration test) The above batteries were charged at a constant current of 0.1C in an environment of 25°C until the battery voltage reached 4.3V. Next, in an environment of 25°C, the tip of a round nail (diameter 1mm) was pierced into the center of the side of the charged sample at a speed of 0.1mm / sec, and the nail was stopped 5mm after it had penetrated the case. The rate at which gas was generated from the battery at that time was measured. The gas generation rate was calculated based on the differential value of the pressure measured by the pressure sensor. Table 1 shows a part of the configuration of each of the above samples and the measurement results of the gas generation rate. The "Deposited Li" for the negative electrode in Table 1 indicates that the negative electrode is a type of electrode in which lithium metal is precipitated during charging.
[0112] [Table 1]
[0113] The gas generation rates in Table 1 are values when the gas generation rate of Battery C1 (volume of gas generated per unit time) is taken as 100%. Gas generation during the nail penetration test is thought to be caused by heat generated by the reaction between oxygen gas released from the positive electrode and lithium metal, and by decomposition of the electrolyte. It is thought that the higher the gas generation rate, the higher the temperature rise of the battery in the event of an abnormality.
[0114] As shown in Table 1, battery C1, which has lithium metal precipitated on the negative electrode, had a higher gas generation rate than battery R1, which uses a negative electrode active material (graphite) that absorbs and releases lithium ions. This suggests that a separator different from the conventional shutdown separator is desirable for lithium secondary batteries, which have lithium metal precipitated on the negative electrode.
[0115] Compared with battery C1, the batteries of this embodiment (batteries A1 to A5) had a lower gas generation rate, which is believed to be because the separators of batteries A1 to A5 contained the above-mentioned functional layer.
[0116] Comparing Battery A1 and Battery A4, the gas generation rate of Battery A1 was significantly lower, suggesting that the effect of the first layer was due to the lithium phosphate particles.
[0117] Comparing Battery A1 and Battery A5, the gassing rate of Battery A1 was significantly lower, suggesting that polymer (PL), especially aramid, is preferable as the main component of the second layer.
[0118] Comparing Battery A2 and Battery A3, the gassing rate of Battery A3 was lower, suggesting that the thickness of the first layer is preferably greater than 2 μm. [Industrial Applicability]
[0119] The present disclosure can be used in lithium secondary batteries. [Explanation of symbols]
[0120] 10 positive electrode 11 Positive electrode current collector 12 Cathode active material layer 20 negative electrode 21 Negative electrode substrate 22 Lithium Metal 30 Separator 31 Base material 32 Functional Layer 32a First Layer 32b Second Layer 40 electrode groups 100 Lithium secondary battery S space
Claims
1. A lithium secondary battery including a positive electrode, a negative electrode, a separator disposed between the positive electrode and the negative electrode, and a non-aqueous electrolyte, the negative electrode is an electrode into which lithium metal is deposited during charging and into which the lithium metal dissolves during discharging; The separator includes a substrate and a functional layer laminated on the substrate, the functional layer includes a first layer including particles of a lithium-containing phosphate; The positive electrode includes a positive electrode active material, The positive electrode active material contains a layered rock-salt type composite oxide containing nickel element, represented by the general formula Li a Ni x Co y M 1-x-y O 2 (wherein 0.97<a≦1.2, 0.5≦x≦1.0, and 0≦y≦0.1 are satisfied, and M is at least one selected from the group consisting of Mn, Al, W, Mg, Mo, Nb, Ti, Si, and Zr), The functional layer further includes a second layer disposed between the substrate and the first layer, The second layer comprises at least one polymer selected from the group consisting of aromatic polyamide, aromatic polyimide, and aromatic polyamideimide.
2. 2. The lithium secondary battery according to claim 1, wherein the phosphate is lithium phosphate.
3. 3. The lithium secondary battery according to claim 1, wherein the content of said phosphate particles in said first layer is in the range of 85% by mass to 99% by mass.
4. 4. The lithium secondary battery according to claim 1, wherein the second layer further contains inorganic particles other than the phosphate particles.
5. 5. The lithium secondary battery according to claim 1, wherein the non-aqueous electrolyte contains lithium ions and anions, and the anions contain at least an anion of an oxalate complex.
6. 6. The lithium secondary battery according to claim 5, wherein the anion of the oxalate complex is a bisoxalate borate anion.
Citation Information
Patent Citations
Composite separator and application thereof in lithium ion battery
CN107093693A
Lithium-sulfur battery
CN107665966A
Lithium secondary battery
JP2001243957A
Lithium ion battery and separator, and battery pack, electronic device, electric vehicle, power storage device, and electric power system
JP2013114764A
High heat-resistant composite separator for lithium secondary batteries and lithium secondary batteries containing the same
JP2015505137A